읽기학습장애의 개념과 진단 평가에 대한 통합 초등학교 교사들의 인식 - 이재호(Jae Ho Lee); 이우진(Woo Jin Lee) (언어치료연구, 2020)
목적: 본 연구는 한국 초등학교에서 학습장애로 진단하는 수가 급격히 감소하고 있는 현실을 통하여 그에 대한 통합 초등학교 일반교사들의 인식을 살펴보고 대안과 함의점을 찾아보고자 하는데 그 목적이 있다. 방법: 연구 참여자는 통합학습 일반 교사로 교육경력 7년에서 27년으로 평균 18.5년의 경력을 가지고 있으며 읽기학습장애 학생 혹은 읽기에 어려움이 있는 학생들을 지도한 경험이 있는 9명의 교사를 대상으로 하였다. 연구도구로는 4개의 주제를 통한 반 구조화된 개방형 질문을 사용하여 교사들의 의견을 수집하여 유목화 하였다. 결과: 연구결과는 다음과 같다. 첫째, 학습장애에 대한 인식에서 학습장애 진단검사 객관성 부족과 학부모 대상 학습장애에 대한 이해가 필요로 하였다. 둘째, 특수교육지원대상의 확대로는 특수교육 지원 대상 범위 확대의 필요성과 특수교육 지원 대상 범위에 대한 축소를 요구하였다. 셋째, 읽기학습장애에 대한 효과적인 선별 방법으로는 읽기학습장애 진단 검사 전문 인력배치와 공식적이고 체계적인 평가도구시스템 개발을 논하였다. 넷째, 읽기학습장애 교육의 질 제고를 위한 교과교육의 방향으로는 교육과정 재구성, 다양한 읽기 경험의 제공이 필요하다는 것을 알 수 있었다. 결론: 본 연구 결과를 통해 통합 학급 초등학교 교사들은 학습장애 및 읽기학습장애에 대한 인식과 진단 및 실태, 효과적인 진단방법에 대한 합의점을 알 수가 있었다. 그리고 교육의 질 제고를 위한 교과교육의 방향성과 체계적인 지원방안을 알 수 있었다. Purpose: The study aims to examine the present declining rate of students diagnosed with learning disabilities (LDs) in Korea though an analysis of interviews with inclusive school students. Methods: The participants in the study were teachers of integrated classes with an average of 18.5 years of educational experience ranging from a low of seven years of experience to a high of 27 years. Nine teachers had experience teaching students with reading disabilities or reading learning disabilities. The research tool was a semi-structured, open-ended questionnaire composed of four topics related to reading and learning disabilities. The interview results were normalized according to the subject of teachers' opinions. Results: First, in the recognition of learning disabilities, lack of objectivity for diagnostic tests of learning disabilities and understanding of learning disabilities for parents were required. Second, there were opinions that it was necessary to expand the scope of support for special education and various opinions on the scope of support. Third, teachers suggested the placement of specialized personnel for reading learning disability diagnosis test and the development of a formal and systematic evaluation tool system as an effective screening method for reading learning disabilities. Fourth, it is necessary to reorganize the curriculum and to provide various reading experiences as the direction of subject education to improve the quality of education for reading learning disabilities. Conclusions: Through this study, elementary school teachers in integrated classrooms were able to find out the perception, diagnosis and actual conditions of learning disabilities and reading disabilities, and opinions on effective diagnosis methods. In addition, the direction of subject education and systematic support plans for improving the quality of reading education were found. KCI Citation Count: 0